HIGH VARIETY VS LOW VARIETY CULTURE IN THE ARABIC LANGUAGE : THE TENSIONS BETWEEN FUSHí‚ AND ‘í‚MIYYA IN THE CONTEMPORARY ARAB WORLD - Yoyo, Yoyo; Mukhlis, Abdul; Thonthowi, Thonthowi; Ferawati, Ferawati (Arabi : Journal of Arabic Studies, 2020)
Arabic language, in its sociological context is divided into two varieties: fusha and ‘amiyya. Arabic fusha is the official language and perceived as the language of Islam. In contrast to the fusha, ‘amiyya is the language used by the Arab people in their daily conversations. However, this ‘amiyya is considered as inferior. The method used in this study was qualitative that stressed the interaction between language and its sociological context. The method assumed that social and political events affected language use in a particular society. The paper tries to re-popularize the two terms used by Ferguson that are "high variety" (H) and "low variety” (L) culture in analyzing the two languages varieties. Besides, the paper explores the tension of the two languages through contemporary social and political events taking place in the Arab World. The Arabic fusha is perceived as a representation of "H” culture because it is a language used in religious literature and official writings, while the ‘amiyya referred to as a representation of "L” variety culture because it is used only as a medium of regular communication.